Vitamin D in Systemic Lupus Erythematosus: Modest Association With Disease Activity and the Urine Protein‐to‐Creatinine Ratio. Issue 7 (2nd July 2013) - Petri, Michelle; Bello, Kayode J.; Fang, Hong; Magder, Laurence S.
Abstract : Objective: To investigate whether an increase in vitamin D levels in patients with systemic lupus erythematosus (SLE) was associated with improvement in disease activity. Methods: A total of 1, 006 SLE patients were monitored over 128 weeks. SLE patients with low levels of 25‐hydroxyvitamin D (25[OH]D; <40 ng/ml) were given supplements of 50, 000 units of vitamin D2 weekly plus 200 units of calcium/vitamin D3 twice daily. Longitudinal regression models were used to estimate the association between levels of 25(OH)D and various measures of disease activity. Results: The SLE patients had the following characteristics: 91% were female, their mean age was 49.6 years, and their ethnicity was 54% Caucasian, 37% African American, and 8% other. For those with levels of 25(OH)D <40 ng/ml, a 20‐unit increase in the 25(OH)D level was associated with a mean decrease of 0.22 (95% confidence interval [95% CI] −0.41, −0.02) ( P = 0.032) in the Safety of Estrogens in Lupus Erythematosus National Assessment (SELENA) version of the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI). This corresponded to a 21% decrease in the odds of having a SELENA–SLEDAI ≥5 (95% CI 1, 37). The mean urine protein‐to‐creatinine ratio decreased by 2% (95% CI −0.03, −0.01) ( P = 0.0001), corresponding to a 15% decrease in the odds of having a ratio >0.5 (95% CI 2, 27). Conclusion: We found that a 20‐ng/ml increase in the 25(OH)D level was associated with a 21% decrease in the odds of having a high disease activity score and a 15% decrease in the odds of having clinically important proteinuria. Although these associations were statistically significant, the clinical importance is relatively modest. There was no evidence of additional benefit of 25(OH)D beyond a level of 40 ng/ml.